2018
DOI: 10.1124/jpet.118.253666
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin, an SGLT2 Inhibitor, Reduced the Mortality Rate after Acute Myocardial Infarction with Modification of Cardiac Metabolomes and Antioxidants in Diabetic Rats

Abstract: The mechanism by which SGLT2 inhibitors reduce cardiac events in diabetic patients remains unclear. Here, we examined the effects of an SGLT2 inhibitor on the acute survival rate after myocardial infarction (MI) in an animal model of type 2 diabetes mellitus (DM) and the possible involvement of modification of cardiac metabolomes and antioxidative proteins. MI was induced in DM Otsuka Long-Evans Tokushima Fatty (OLETF) rats and Long-Evans Tokushima Otsuka (LETO) control rats. Treatment with empagliflozin (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 42 publications
4
64
0
3
Order By: Relevance
“…Furthermore, it has been found that the utilization rate of ketone bodies is reduced during the course of myocardial ischemia [33]. Studies have suggested that increasing the use of ketone bodies, fatty acid, and branched-chain amino acids inhibited adenosine triphosphate (ATP) reduction, increasing ATP content in the myocardium in the empagliflozin group [34]. In the present study, the serum ketone bodies were also increased in the empagliflozin group, which may have resulted in the decreased myocardial oxygen consumption and decreased cardiac sympathetic nerve activity in patients with AMI being administered empagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that the utilization rate of ketone bodies is reduced during the course of myocardial ischemia [33]. Studies have suggested that increasing the use of ketone bodies, fatty acid, and branched-chain amino acids inhibited adenosine triphosphate (ATP) reduction, increasing ATP content in the myocardium in the empagliflozin group [34]. In the present study, the serum ketone bodies were also increased in the empagliflozin group, which may have resulted in the decreased myocardial oxygen consumption and decreased cardiac sympathetic nerve activity in patients with AMI being administered empagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, acute hyperglycemia exaggerates inflammation by the oxidative mechanism [27]. Animal experiments show that SGLT2 inhibitors can reduce the mortality of myocardial infarction in diabetic mice through cardiac energy metabolism and protective modification of antioxidant proteins, suggesting that hyperglycemia is associated with energy metabolism disorder and oxidative stress in myocardial infarction [28]. Risso reported that intermittent high glucose enhanced apoptosis of human endothelial cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anti-diabetic drugs can either confer cardioprotection or interfere with endogenous cardioprotection & Penna, 2011;Skyschally et al, 2009). IPost has been reported to confer cardioprotection via the production of several different autacoids (such as bradykinin, adenosine and opioids), which recruit known cardioprotective signalling pathways (such as the SAFE, NO/PKG and RISK cascades) and which converge on the mitochondrial permeability transition pore (Bell et al, 2016;Boengler, Heusch, & Schulz, 2011;Cohen & Downey, 2011;Lacerda, Opie, & Lecour, 2012;Oosterlinck et al, 2013;Pagliaro et al, 2011;Penna et al, 2015).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%